2010
DOI: 10.1111/j.1524-4733.2010.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Cost–Utility Analysis of Topical Intranasal Steroids for Otitis Media with Effusion Based on Evidence from the GNOME Trial

Abstract: Topical steroids are unlikely to be a cost-effective treatment for OME in general practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Illustrates potential for differing conclusions between CMA and CEA 2 GNOME (Petrou et al, 2010;Williamson et al, 2009a): placebo-controlled RCT on intranasal steroids for otitis media (n = 217) Differences in costs and effectiveness are negligible and nonsignificant 3 10 simulated datasets Highlight situations where differences in uncertainty estimates between CMA and CEA are particularly large or small or when there may be a significant difference in net benefits despite no significant differences in costs or effects…”
Section: Empirical Studymentioning
confidence: 98%
See 3 more Smart Citations
“…Illustrates potential for differing conclusions between CMA and CEA 2 GNOME (Petrou et al, 2010;Williamson et al, 2009a): placebo-controlled RCT on intranasal steroids for otitis media (n = 217) Differences in costs and effectiveness are negligible and nonsignificant 3 10 simulated datasets Highlight situations where differences in uncertainty estimates between CMA and CEA are particularly large or small or when there may be a significant difference in net benefits despite no significant differences in costs or effects…”
Section: Empirical Studymentioning
confidence: 98%
“…Research Framework] Nasal steroids for Otitis Media with Effusion trial. The GNOME trial observed no significant differences between steroids and placebo for costs, QALYs, utilities, side effects or the primary clinical endpoint (cure at one month; Petrou et al, 2010;Williamson et al, 2009a). CUA showed steroids to be dominated by placebo, generating non-significantly fewer QALYs and non-significantly higher costs (Table III).…”
Section: Gprf [General Practicementioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have shown that there are considerable differences in ICERs over patient groups, in such diverse areas as children otitis media [26], tuberculosis screening [27], assertive community treatment for homeless people [28] and phosphate binders in end-stage renal disease [29]. The Swedish health economic evaluation recommendations state that “The purpose of a health economic evaluation is to identify for which patient groups or indications a drug is cost-effective –it is never the medication itself which is cost-effective, rather the use of it” ( [14], p. 1).…”
Section: Discussionmentioning
confidence: 99%